Down, Up, and Over: Slave Religion and Black Theology - Hopkins, Dwight N (Department of Religious Studies, 2023)
This thesis answers the following question: In the context of American Protestantism and American culture from 1619 to 1865, how did African American slaves develop a Christian religion? My claim is that enslaved blacks began to fashion a new religion by reinterpreting the Christianity given to them by their Christian slave masters. With their reinterpreted religion they combined their own novel folk culture, which, itself, comprised a mixture of common folk wisdom and some retentions of their West African religio-cultural background. This new black religion had commonalities with the dominant Christianity in American Protestantism and culture. At the same time, however, it accented some dissimilarities; in particular, it underscored the idea of Christianity being a religion for the weak and victims in a society. Also, the ingredients of black religion differed markedly from the dominant mainstream Christianity. Black chattel synthesized the religion and culture of their folk wisdom gained in the New World with their religio-cultural retentions from West Africa. Similarly, in form of worship, black slaves developed religious expressions which entailed more spontaneous body and verbal engagement with what they considered the divine presence among them. Thus in terms of doctrine (e.g., beliefs), sources (e.g., synthesis), and witness ( e.g., practice), black religion evolved into a specific experience of Protestantism in American culture. In sum, the unique religion of black slaves comprised a reinterpreted Christianity from their masters, religiocultural dimensions of their folk experiences in the New World, and partial retentions of West African religions. I develop this thesis by relying mainly on primary documentation. I interpret critically interviews with ex-slaves, autobiographies of blacks who escaped from slavery, songs created by enslaved African Americans (both religious and secular lyrics), folk tales of black slaves, and studies of West African indigenous religions and culture. (The West African region is chosen because the overwhelming numbers of American slaves originated from that location.) Research entails archival investigation at several locations throughout the U.S.A. Secondary sources are from various history books on Christianity and secular society during the years from 1619 to 1865 - from the arrival of the first African slaves to the colonies in the North American New World to the end of the American civil war. In addition, in order to answer my research question and examine my thesis, I argue that the unique black religion crafted by African American slaves consisted of support for the weak and victims of society --- a support for their survival and for their freedom. In order to concretize this survival-freedom claim, I present how black religion manifested survival and freedom on four levels. The first level is political economy and deals with issues of wealth, income, and connections to the political government. The second concerns the notion of power not related to wealth and the political state apparatus. The third level is language; how slaves manipulated language to pursue their own ends. And finally, the idea of racial cultural identity is brought into play. These four levels are chosen because they grow out of my investigations of how slaves understood Christianity as a meshing of both sacred and secular realms without much separation or a sharp dichotomy. These levels are selected also because the primary documentation shows that blacks attempted to create a new religion through these four aspects. The conclusion to the research question is the following. Enslaved blacks created a syncretic Christian religion. In this process they recreated themselves on the political economic, linguistic, every day, and racial-cultural levels. They attempted to constitute a new individual self in conformity with the earthly goal of establishing a new commonwealth.